Inflammatory cytokine mRNA detection by real time PCR in chorioamniotic membranes from pregnant women with preterm premature rupture of membranes - Polettini, J. [UNESP]; Peraçoli, José Carlos [UNESP]; Candeias, J. M. G.; Araujo Junior, J. P.; Silva, Marcia Guimarães da [UNESP] (Elsevier B.V., 2009)
Objective: To quantify the expression of interleukin (IL)-1 beta, IL-6, IL-8 and tumor necrosis factor alpha (TNF-alpha) in chorioamniotic membranes of PPROM pregnant women with chorioamnionits.Study design: The study included 25 PPROM women in labor, 15 PPROM without labor, and 25 pregnant women in preterm labor (PTL). Chorioamniotic membranes were collected for histopathological analyses and cytokine mRNA expression quantification by real time PCR. Comparisons were performed using the Mann-Whitney, Kruskal-Wallis, Fisher's exact test or z test with significance set at p < 0.05. The software employed was the SigmaStat version 3.1.Results: During the study PPROM incidence was 4.6% and chorioamnionits was present in 75% of the samples. IL-1 beta, IL-6, and IL-8 mRNA expression did not statistically differ among study groups. TNF-alpha mRNA expression was statistically higher in PTL. No difference in the mRNA concentration of the cytokines studied in the presence of chorioamnionitis was observed.Conclusion: Chorioamniotic membranes are sources of IL-1 beta, IL-6, IL-8, and TNF-alpha and their mRNA concentrations in PPROM are not related to the presence of chorioamnionitis. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Preterm premature rupture of membranes; Chorioamnionitis; Cytokines; Real time PCR